Pengaruh Work Life Balance Dan Work Environment Terhadap Employee Performance Dengan Job Satisfaction Sebagai Variabel Mediasi Pada PR. Berkah Sejagat Sumenep - Haliza, Siti Nur; Asiyah, Siti; Bastomi, Mohamad (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This research was conducted to determine the influence of work life balance and work environment on employee performance through job satisfaction. The method used in this research is a quantitative method with an explanatory research type. The population of this research is employees of PR Berkah Sejagat Sumenep with a sample size of 50 respondents obtained using the saturation technique. This research uses the Structural Equation Modeling (SEM) data analysis method with the help of SmartPLS 4.1.0.9 software. The results of this research show that work life balance has no effect on employee performance, work environment has an effect on employee performance, work life balance has no effect on job satisfaction, work environment has an effect on job satisfaction, job satisfaction has an effect on employee performance, work life balance has no effect on employee performance through job satisfaction, and work environment has an effect on employee performance through job satisfaction. Keywords: Employee Performance, Work Life Balance, Work Environment, Job Satisfaction, PR Berkah Sejagat